Influences of Allocating HIV/AIDS Specialized Nurses on Clinical Outcomes in Japan - Masakazu Nishigaki, PhD, RN; Yuko Sugino, PhD, RN; Jongmi Seo, MHS, RN; Megumi Shimada, PhD, RN; Kazuko Ikeda, PhD, RN; Keiko Kazuma, PhD, RN (Elsevier, 2011)
This retrospective cohort study was conducted to demonstrate how allocation of nurses specialized in HIV care influences clinical outcomes of antiretroviral therapy (ART) for people living with HIV (PLWH). Methods: The medical records of 116 PLWH who started ART between January 2002 and December 2004 were analyzed. Occurrence of viral suppression and viral relapse after suppression achievement and their time from baseline were observed as clinical outcomes related to ART. Clinical outcomes were obtained from medical records between January 2002 and December 2006. PLWH were classified into two groups according to allocation (n = 95, nurse allocated group) or nonallocation (n =21, nurse nonallocated group) of nurses specialized in HIV. Results: Survival analysis showed that HIV viral load was suppressed more rapidly and continuously in nurse allocated group than nonallocated group (p < .0001). Viral relapse after suppression achievement occurred easily in nurse nonallocated group than allocated group (p = .003). Conclusions: The present findings demonstrated that the role of specialized nurses is critically important from the viewpoint of clinical outcome.